Consonant and Vowel Confusions in Well-Performing Children and Adolescents With Cochlear Implants, Measured by a Nonsense Syllable Repetition Test - Rødvik, Arne Kirkhorn; Tvete, Ole; Torkildsen, Janne von Koss; Wie, Ona Bø; Skaug, Ingebjørg; Silvola, Juha Tapio (Frontiers in Psychology, 2019)
Although the majority of early implanted, profoundly deaf children with cochlear implants (CIs), will develop correct pronunciation if they receive adequate oral language stimulation, many of them have difficulties with perceiving minute details of speech. The main aim of this study is to measure the confusion of consonants and vowels in well-performing children and adolescents with CIs. The study also aims to investigate how age at onset of severe to profound deafness influences perception. The participants are 36 children and adolescents with CIs (18 girls), with a mean (SD) age of 11.6 (3.0) years (range: 5.9–16.0 years). Twenty-nine of them are prelingually deaf and 7 are postlingually deaf. Two reference groups of normal-hearing (NH) 6- and 13-year-olds are included. Consonant and vowel perception is measured by repetition of 16 bisyllabic vowel-consonant-vowel nonsense words and 9 monosyllabic consonant-vowel-consonant nonsense words in an open-set design. For the participants with CIs, consonants were mostly confused with consonants with the same voicing and manner, and the mean (SD) voiced consonant repetition score, 63.9 (10.6)%, was considerably lower than the mean (SD) unvoiced consonant score, 76.9 (9.3)%. There was a devoicing bias for the stops; unvoiced stops were confused with other unvoiced stops and not with voiced stops, and voiced stops were confused with both unvoiced stops and other voiced stops. The mean (SD) vowel repetition score was 85.2 (10.6)% and there was a bias in the confusions of [iː] and [yː]; [yː] was perceived as [iː] twice as often as [yː] was repeated correctly. Subgroup analyses showed no statistically significant differences between the consonant scores for pre- and postlingually deaf participants. For the NH participants, the consonant repetition scores were substantially higher and the difference between voiced and unvoiced consonant repetition scores considerably lower than for the participants with CIs. The participants with CIs obtained scores close to ceiling on vowels and real-word monosyllables, but their perception was substantially lower for voiced consonants. This ¬may partly be related to limitations in the CI technology for the transmission of low-frequency sounds, such as insertion depth of the electrode and ability to convey temporal information.